Ion sputtering for preparation of thin MAX and MXene phases. Issue 1 (2nd January 2020) - Vacík, J.; Horák, P.; Bakardjieva, S.; Bejsovec, V.; Ceccio, G.; Cannavo, A.; Torrisi, A.; Lavrentiev, V.; Klie, R.
Abstract : Thin films of MAX and MXene phases were prepared by ion beam sputtering followed by thermal annealing in vacuum. For this purpose, a Low Energy Ion Facility (LEIF) using heavy ions for target irradiation was developed, and the DC ion beam sputtering method was implemented. The process for preparing MAX and MXene thin composites consists of two steps. First step: bombarding the elemental targets with low-energy ions (either all targets together, each with the corresponding size, or each target separately and repeatedly); it results in synthesis of either homogeneous layers of mixed phases or multilayer arrays of individual phases. Second step: thermal annealing under vacuum with a suitable temperature and time to induce a diffusion process, mutual phase interaction and finally the formation of MAX or MXene composites with the desired structure. After installation of the LEIF system and the introduction of the two-step method, i.e. DC ion sputtering with subsequent thermal processing, the first Ti-based MAX and MXene carbides, Ti2 SnC and Ti2 C, in thin films of composites were prepared and analyzed.